Fitness Level and Not Aging per se, Determines the Oxygen Uptake Kinetics Response - George, Mitchell A.; McLay, Kaitlin M.; Doyle-Baker, Patricia K.; Reimer, Raylene A.; Murias, Juan M. (Frontiers in Physiology, 2018)
Although aging has been associated to slower V̇O2 kinetics, some evidence indicates that fitness status and not aging per se might modulate this response. The main goal of this study was to examine the V̇O2, deoxygenated hemoglobin+myoglobin (deoxy-[Hb+Mb]) kinetics, and the NIRS-derived vascular reperfusion responses in older compared to young men of different training levels (i.e., inactive, recreationally active, and endurance trained). Ten young inactive (YI; 26 ± 5; peak V̇O2 (V̇O2peak), 2.96 ± 0.55 L·min-1), 10 young recreationally active (YR; 26 ± 6; 3.92 ± 0.33 L·min-1), 10 young endurance trained (YT; 30 ± 4; 4.42 ± 0.32 L·min-1), 7 older inactive (OI; 69 ± 4; 2.50 ± 0.31 L·min-1), 10 older recreationally active (OR; 69 ± 5; 2.71 ± 0.42 L·min-1) and 10 older endurance trained (OT; 66 ± 3; 3.20 ± 0.35 L·min-1) men completed transitions of moderate intensity cycling exercise (MODS) to determine V̇O2 and deoxy-[Hb+Mb] kinetics, and the deoxy-[Hb+Mb]/V̇O2 ratio. The time constant of V̇O2 (τV̇O2) was greater in YI (38.8 ± 10.4 s) and OI (44.1 ± 10.8 s) compared with YR (26.8 ± 7.5 s) and OR (26.6 ± 6.5 s), as well as compared to YT (14.8 ± 3.4 s), and OT (17.7 ± 2.7 s) (p < 0.05). τV̇O2 was greater in YR and OR compared with YT and OT (p < 0.05). The deoxy-[Hb+Mb]/V̇O2 ratio was greater in YI (1.23 ± 0.05) and OI (1.29 ± 0.08) compared with YR (1.11 ± 0.03) and OR (1.13 ± 0.06), as well as compared to YT (1.01 ± 0.03), and OT (1.06 ± 0.03) (p < 0.05). Similarly, τV̇O2 was greater in YR and OR compared with YT and OT (p < 0.05). There was a main effect of training (p = 0.033), whereby inactive (p = 0.018) and recreationally active men (p = 0.031) had significantly poorer vascular reperfusion than endurance trained men regardless of age. This study demonstrated not only that age-related slowing of V̇O2 kinetics can be eliminated in endurance trained individuals, but also that inactive lifestyle negatively impacts the V̇O2 kinetics response of young healthy individuals.